2017
DOI: 10.15619/nzjp/45.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Rotator cuff repair protocols: A survey of current New Zealand practice

Abstract: Rehabilitation following surgical rotator cuff repair may enable return to pre-injury function. Optimal recovery is facilitated by the use of post-operative protocols that enhance communication between the surgeon and physiotherapist. The purpose of this study was to describe the rotator cuff repair rehabilitation protocols currently used in New Zealand. Orthopaedic surgeons practising in New Zealand were contacted to determine their current rehabilitation protocols. Length of immobilisation and exercise progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Therefore, we could not calculate view, participation and completion rates. The results from our study for sling usage were similar to those found in the UK, 8 New Zealand 13 and reflect the findings from Vieira et al 10 that 67% of shoulder surgeons recommend an immobilization period of 3e6 weeks. Although it is common practice to use a sling for 6 weeks after surgery, there is no high-quality evidence to support this decision.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Therefore, we could not calculate view, participation and completion rates. The results from our study for sling usage were similar to those found in the UK, 8 New Zealand 13 and reflect the findings from Vieira et al 10 that 67% of shoulder surgeons recommend an immobilization period of 3e6 weeks. Although it is common practice to use a sling for 6 weeks after surgery, there is no high-quality evidence to support this decision.…”
Section: Discussionsupporting
confidence: 90%
“…The progression timeline found in our study was similar to two other countries, New Zealand and North America. 9,13 In New Zealand, the majority of the protocols would allow passive exercises in the first week and active exercises at 6e8 weeks. 13 In North America, passive exercise starts within two weeks from surgery and active exercises at 7e10 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations